Beta-HCG Secretion by a Pulmonary Choriocarcinoma in a Male Patient - Brecht Devos; Cedric Willemse; Mira Sterckx; Johan Debruyne; Inge Stappaerts; Tom Van den Mooter; Marjan Hertoghs; Pascale Abrams (Case Reports in Oncological Medicine)
Background. Paraneoplastic secretion of beta-subunit of human chorionic gonadotropin (β-HCG) in pulmonary carcinoma is rare. Case Presentation. A 65-year-old man presented with bilateral gynaecomastia with abnormally high levels of β-hCG and elevated oestradiol, progesterone, and testosterone levels on April 7, 2023. After excluding testicular malignancy, CT scan of the chest and abdomen revealed bilateral pulmonary lesions. Transthoracic biopsy confirmed malignancy with choriocarcinoma. MRI of the brain showed a solitary brain metastasis, while on a subsequent 18F-FDG PET/CT, no other metastatic lesions were seen. The patient was treated with chemoimmunotherapy carboplatin-etoposide-pembrolizumab with good partial response. Conclusion. Our case of a presumably stage IV dedifferentiated mNSCLC presenting as an extragonadal β-hCG secreting pulmonary choriocarcinoma is a very rare tumor with a poor prognosis. Its biology, origin, and treatment remain to be elucidated. Cancer genome sequencing is necessary for the identification of the origin and seeking treatment.